Diet quality as measured by the Diet Quality Index–International is associated with prospective changes in body fat among Canadian children. Issue 3 (23rd September 2016) - Setayeshgar, Solmaz; Maximova, Katerina; Ekwaru, John Paul; Gray-Donald, Katherine; Henderson, Mélanie; Paradis, Gilles; Tremblay, Angelo; Veugelers, Paul
Abstract: Objective: To quantify the association of dietary quality with prospective changes in adiposity. Design: Children participating in the QUALITY (QUebec Adipose and Lifestyle InvesTigation in Youth) study underwent examination at baseline and at 2-year follow-up. Dietary quality was assessed by the Diet Quality Index–International (DQII) using three non-consecutive 24 h diet recalls at baseline. The DQII has four main categories: dietary adequacy, variety, moderation and overall balance. Fat mass index (FMI; [fat mass (kg)]/[height (m)] 2 ), central FMI (CFMI; [trunk fat mass (kg)]/[height (m)] 2 ), percentage body fat (%BF; [total fat mass (kg)]/[total mass (kg)]) and percentage central BF (%CBF; [trunk fat mass (kg)]/[total mass (kg)]) were assessed through dual-energy X-ray absorptiometry. Setting: Children were selected from schools in the greater Montreal, Sherbrooke and Quebec City metropolitan areas between 2005 and 2008, Quebec, Canada. Subjects: A total of 546 children aged 8–10 years, including 244 girls and 302 boys. Results: Regression analysis adjusting for age, sex, energy intake, physical activity and Tanner stage revealed that every 10-unit improvement in overall DQII score was associated with lower gain in CFMI ( β =−0·08; 95 % CI −0·17, −0·003) and %BF ( β =−0·55; 95 % CI −1·08, −0·02). Each unit improvement in dietary adequacy score was associated with lower gain in FMI ( β =−0·05; 95 % CI −0·08, −0·008), CFMI ( β =−0·03; 95 % CI −0·05, −0·007), %BF ( β =−0·15; 95 % CI −0·28, −0·03) and %CBF ( β =−0·09; 95 % CI −0·15, −0·02). Conclusions: Promotion of dietary quality and adequacy may reduce weight gain in childhood and prevent chronic diseases later in life.